Business assessment of managerial potential in the foreign economic activity of the enterprise - Laushkin, A. M.; Mekhovich, S. A.; Pererva, P. G. (My University, 2023)
There are different concepts of the potential of an enterprise or its components: the concept of production potential, personnel potential, economic potential, marketing potential, regional potential, strategic potential. However, only a combination of these concepts can ensure the true competitiveness of the enterprise in foreign markets. The integration of these indicators creates a competitive advantage, which many authors reduce to the main competence of the business structure.
Бізнес-оцінка управлінського потенціалу у зовнішньоекономічній діяльності підприємства
Keywords: management potential; business assessment; international business; efficiency